Anaplastic Lymphoma Kinase-Positive Large B-Cell Lymphoma: An Underrecognized Aggressive Lymphoma. (26th February 2012) - Morgan, Elizabeth A.; Nascimento, Alessandra F.
Abstract : Anaplastic lymphoma kinase-(ALK-) positive large B-cell lymphoma (ALK+ LBCL) is a rare, aggressive tumor characterized by an immunoblastic or plasmablastic morphologic appearance, expression of ALK, CD138, CD45, EMA, and often IgA by immunohistochemistry, and characteristic chromosomal translocations or rearrangements involving the ALK locus. The morphologic and immunophenotypic overlap of this tumor with other hematologic and nonhematologic malignancies may result in misdiagnosis. The tumor has been identified in both pediatric and adult populations and demonstrates a male predominance. Presentation is most often nodal, particularly cervical. No association with immunocompromise or geographic location has been recognized. The most common gene rearrangement is between clathrin and ALK (t(2;17)(p23;q23)), resulting in the CLTC-ALK chimeric protein, although other fusions have been described. Response to conventional chemotherapy is poor. The recent introduction of the small molecule ALK inhibitor, crizotinib, may provide a potential new therapeutic option for patients with this disease.